Disruption of chromatin organisation causes MEF2C gene overexpression in intellectual disability: a case report - Kevin Yauy; Anouck Schneider; Bee Ling Ng; Jean-Baptiste Gaillard; Satish Sati; Christine Coubes; Constance Wells; Magali Tournaire; Thomas Guignard; Pauline Bouret; David Geneviève; Jacques Puechberty; et al. (BMC, 2019)
Abstract Background Balanced structural variants are mostly described in disease with gene disruption or subtle rearrangement at breakpoints. Case presentation Here we report a patient with mild intellectual deficiency who carries a de novo balanced translocation t(3;5). Breakpoints were fully explored by microarray, Array Painting and Sanger sequencing. No gene disruption was found but the chromosome 5 breakpoint was localized 228-kb upstream of the MEF2C gene. The predicted Topologically Associated Domains analysis shows that it contains only the MEF2C gene and a long non-coding RNA LINC01226. RNA studies looking for MEF2C gene expression revealed an overexpression of MEF2C in the lymphoblastoid cell line of the patient. Conclusions Pathogenicity of MEF2C overexpression is still unclear as only four patients with mild intellectual deficiency carrying 5q14.3 microduplications containing MEF2C are described in the literature. The microduplications in these individuals also contain other genes expressed in the brain. The patient presented the same phenotype as 5q14.3 microduplication patients. We report the first case of a balanced translocation leading to an overexpression of MEF2C similar to a functional duplication.